Keanekaragaman Makrozoobentos Di Pesisir Pantai Desa Panggung Kecamatan Kedung Kabupaten Jepara - IZZAH, Nisrina Arifatul, Efri Roziaty, S. Si., M. Si (2016)
This research was about the marozoobenthos diversity in Panggung beach, Kedung, Jepara conducted in March until April 2016. The purpose of this research was to investigated the rate of diversity macrozoobenthos. This research was using purposive sampling to determine the location and using line transect to determine plots. There were two main station 1 and stations named station I and station II. The study found 6 species consist of 2 species Bivalvia class (Phyllum Mollusca), they were Anadara granosa dan Scrobicularia plana, 2 Species Gastropoda (Phyllum Mollusca), they were Turritella nivea and Quoyia decollata, 1 from Crustacea (Phyllum Arthropoda) it was Penaeus indicus and 1 from Polychaeta Class (Phyllum Annelida) it was Arenicola marina. Species composition,c population density, diversity and evenness of species macrozoobenthos comunities in the station 1 higher than station 2. The result of analyze founded Indeks of diversity ( H') macrozoobentos in station I (1,52) and station II (1,47). Both stations showed the result 1 < H < 2 indenticate low diversity and the quality of sea water environment a half polluted. The environmental quality of sea in seashore around Panggung beach,Kedunng Jepara needs attention to reduce the impact of environmental pollution.